Average annual costs of Rheumatoid Arthritis estimated by inverse probability weighting and their influence factors: A cross-sectional study based on Chinese Registry of Rheumatoid arthritis (CREDIT) Cohort - Bing Yu; Lin Qiao; Lu Li; Keying Zuo; Liangming Li; Li Wang; Nan Jiang; Qian Wang; Mengtao Li; Yanhong Wang; Xinping Tian (PLoS ONE, 2025)
Objective To date, the evidences of economic burden for the RA individual in the real-world clinical practice were still limited in China. This study aimed to estimate average annual costs of rheumatoid arthritis (RA) patients using inverse probability weighting (IPW) and their influence factors. Methods A multicenter, cross-sectional study was conducted and the RA patients who met inclusion criteria on CREDIT cohort were invited to participate the survey. After they signed the informed confirm form, the information of outpatient and inpatient expenditures in the past year were collected through online questionnaires. Medical records were retrieved from the Chinese Rheumatology Information System (CRIS). Propensity scores for sample using the Generalized Boosted Model (GBM) method were used to calculate IPW, so that we produced the weighted population similar to the target of RA patients on CREDIT. Bootstrap methods were used to estimate average costs and 95% confidence intervals with 1,000 samples. Indirect costs were estimated using the human capital approach. Weighted multivariate regression identified factors influencing average annual costs. Results In this study, a total of 18,507 patients from the CREDIT database met the recruitment criteria. Among them, 1,293 patients from 152 hospitals across 29 provinces in China completed the questionnaire and were included in our analysis. The average annual total costs per patient by the Bootstrap method on the weighted population was about 41,971 CNY (Bootstrap 95%CI: 37,107–47,046 CNY), in which more than 75% were the direct costs. Moreover, in the direct costs, the medical costs accounted for nearly 89% and even half of them (approximately 59.7%) was medication expense. The moderate or high disease activity status, hospitalization in last year, history of comorbidity, the treatment of biologics or glucocorticoids were also found to substantially increase average annual costs of RA in our study. Conclusions This study provided reliable insight into evaluating the economic burden of RA for the individuals and their families in the real-world clinical practice of China.